2015
DOI: 10.1016/j.jnoncrysol.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids at charged surfaces: Insight from molecular simulations

Abstract: Understanding of molecular level structure and mechanisms of the formation of electric double layers in realistic ionic liquid-based electrolytes on charged electrode surfaces is one of scientifically and technologically key areas that has attracted a lot of attention over the last decade. Extensive experimental, theoretical, and modeling studies have been dedicated to this challenging topic in order to establish fundamental correlations between the details of molecular structure of electrolyte and the propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 54 publications
7
36
0
Order By: Relevance
“…Even more important is the unique usefulness and the plethora of complementary information when we consider the advanced stage of modeling that now even taps into charge/discharge kinetics and adopts more realistic pore networks. 4,[56][57][58] Yet, most experimental techniques fall short to provide a molecular picture of the ion electrosorption process and we believe that our approach adds an advanced technique to the limited number of electrochemical in situ methods. More generally, this novel approach might be of interest for a variety of fields where ion adsorption within confined geometry plays an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Even more important is the unique usefulness and the plethora of complementary information when we consider the advanced stage of modeling that now even taps into charge/discharge kinetics and adopts more realistic pore networks. 4,[56][57][58] Yet, most experimental techniques fall short to provide a molecular picture of the ion electrosorption process and we believe that our approach adds an advanced technique to the limited number of electrochemical in situ methods. More generally, this novel approach might be of interest for a variety of fields where ion adsorption within confined geometry plays an important role.…”
Section: Discussionmentioning
confidence: 99%
“…However, in both studies, the structural difference becomes significant when the potential difference is high (over 5 V) . The constant‐potential method is about one order of magnitude slower than the constant‐charge method, but it allows MD simulations to explore more complex and inhomogeneous electrode systems, such as rough surfaces, activated carbon and amorphous carbide‐derived carbons (CDCs), where the constant‐charge method is not applicable.…”
Section: Classical Methods To Simulate Edlcsmentioning
confidence: 99%
“…The simplified electrode models in the CMD simulations usually lead to lower capacitances . Vatamanu and coworkers showed that the surface roughness (Figure e) could increase the energy storage . Palmer and coworkers conducted quench molecular dynamics (QMD) simulations to generate porous carbon models by mimicking the thermal quenching of systems of carbon atoms .…”
Section: Edl Capacitance Inside Nanoporesmentioning
confidence: 99%
“…The effect of substrates was further extended to the capacitive properties of graphene‐based systems. Based on the as‐obtained electrolyte structuring, the electric potential of single electrode U electrode was computed, defined as the potential drop within electrode/electrolyte interfacial district relative to the potential of zero charge ( PZC ), [Eq. ]: trueUelectrode=UEDL-PZC …”
Section: Resultsmentioning
confidence: 99%
“…[34,35] Nevertheless, the density oscillations became vanished about~12 Å away from the electrode surface, consistent with previous theoretical studies. [24,36] Noteworthy, according to prior theoretical studies [37,38] , the capacitive behaviors of EDLCs were predominantly determined by the electrolyte distributions in the first layer or interfacial districts at the nanoscale, indicating that the contributions of ionic density profiles from second peak to bulk region were rather marginal. For example, based on the ion number within the first layer, Jo and colleagues have proposed a novel and useful measurement (i. e., differential ion capacity) to interpret the as-obtained capacitive results well.…”
Section: Substrate Effects On the Edl Structuresmentioning
confidence: 95%